Effects of pre-harvest application of melatonin, 24-epibrassinolide, and methyl jasmonate on flavonoid content in blueberry fruit - Zheng, Hui; Yang, Yong; Wu, Sizheng; Jia, Fan; Jiang, Jiani; Yu, Lin; Ou, Guangmei; Shu, Man; Qin, Wei (Frontiers in Nutrition, 2024)
The application of plant growth regulators is an effective method to enhance flavonoid content in certain fruits; however, there is limited research comparing the effects of different plant growth regulators. This study evaluated the impact of pre-harvest application with melatonin, 24-epibrassinolide, and methyl jasmonate on flavonoid content in blueberry fruit. All three plant growth regulators increased the total polyphenol content, total flavonoid content, antioxidant capacities, and the activities of key enzymes involved in flavonoid biosynthesis, including flavone synthase, flavanone 3-hydroxylase, flavonol synthase, anthocyanidin synthase, and leucoanthocyanidin reductase. Among these, melatonin exhibited the most significant effect. Further comparative analyses showed that 0.5 mM melatonin was particularly effective in promoting the accumulation of flavonols, anthocyanins, and flavanones, as well as specific compounds such as avicularin, astragalin, morin, and reynoutrin in blueberry fruit, whereas 1.0 μM 24-epibrassinolide was more effective in enhancing the accumulation of flavones and flavanols, such as quercetin, leucocyanidin, phloretin, and epicatechin. In general, melatonin resulted in a greater enhancement of flavonoid content in blueberry fruit compared to 24-epibrassinolide and methyl jasmonate. This study highlights the distinct effects of these three plant growth regulators on flavonoid accumulation in blueberry fruit, providing valuable insights for the production of high-quality blueberries.